Shift and share analysis of regional employment change in Ireland, 1951-66 - O'Farrell, PN (Economic & Social Studies, 1972)
If regional policy in Ireland is to be developed so as to become more effective, or even if the goal is to evaluate existing strategies the logical first step is to consider the underlying causes of regional disparities in social and economic welfare. Obviously the symptoms of regional distress in Ireland - low incomes, high net emigration, high unemployment and underemployment - could all be alleviated by a faster rate of economic expansion in the regions - but this begs the question as to the cause of inadequate growth in the regions.
Keywords: Employment; Ireland